Effects of phytosterol ester supplementation on egg weight, biochemical indices, liver immunity and gut microbiota of laying hens during peak laying period - Wenzi Wu; Zhuo Chen; Qixin Huang; Rui Chen; Xin Ma; Wenxin Ye; Jinghui Fan; Lichun Qian (Poultry Science)
ABSTRACT: This experiment was aimed to investigate the effects of Phytosterol Ester (PSE) supplementation on egg weight, biochemical indices, liver immunity and gut microbiota of Hy-Line Brown laying hens during peak laying period. A total of 256 healthy Hy-Line Brown laying hens were randomly allocated into 4 groups. Laying hens in the control group were fed a basal diet (CON), while those in the experimental groups received a basal diet containing 10 mg/kg (PSE10), 20 mg/kg (PSE20), or 40 mg/kg (PSE40) mg/kg PSE, respectively. We found that PSE supplementation significantly increased the egg weight in PSE20 and PSE40 groups (P < 0.05) and the serum magnesium (Mg) content in PSE10 and PSE20 groups (P < 0.05), but significantly decreased the serum calcium (Ca) content in PSE40 group (P < 0.05). Moreover, PSE supplementation significantly increased the total protein (TP) content of ovary in all experimental groups (P < 0.01) and decreased the total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) contents of the ovary in PSE20 and PSE40 groups (P < 0.001). In serum, PSE supplementation significantly increased TP content in all experimental groups (P < 0.01) and albumin (ALB) content in PSE20 group (P < 0.05). Alkaline phosphatase (AKP) in PSE20 group, TC content in all experimental groups and LDL-C content in PSE20 and PSE40 groups were significantly decreased (P < 0.05). In egg yolk, PSE supplementation significantly increased TP content in PSE20 and PSE40 groups (P < 0.01) and decreased TC content in PSE20 group (P < 0.01). In liver immunofluorescence, PSE supplementation altered the content of CD163, especially in PSE20 group. Dietary PSE significantly decreased the relative abundance of Bacteroides and Desulfovibrio, while increased the relative abundance of Faecalibacterium, g_unclassified_f_Lachnospiraceae, g_norank_f_Ruminococcaceae, g__unclassified_f__Oscillospiraceae and other bacteria. In conclusion, PSE supplementation increased the average egg weight and total protein, lowered egg yolk, serum and ovary cholesterol of Hy-Line Brown laying hens. At the same time, it can also promote serum magnesium levels, enhanced liver immunity, and improved gut microflora.